Using the Input - Output Model in building the economic plan using the computer - خلف, م.د.باسل احمد (Journal of Planner and Development, 2007)
The origin of this technique lies in the analysis of François Kenai (1694-1774), the leader of the School of Naturalists, presented in Tableau Economique. This method was developed by Karl Marx in his analysis of the Departmental Relationships and the nature of these relations in the models of " "He said. The current picture of this type of economic analysis is credited to the Russian economist Vasily Leontif. This analytical model is commonly used in developing economic plans in developing countries (p. 1, p. 86). There are several types of input and output models, such as static model, mobile model, regional models, and so on. However, this research will be confined to the open-ended model, which found areas in practical application. It is well known that the term "static" refers to models that do not explicitly take time into account. This model does not show capital accumulation over time. The term "open" refers to the existence of a number of variables (mainly the components of the final request) that are determined outside the model (M 2, p. 47/48). The aim of this research is to focus on the most important uses of the user / product model in building the national economy plan, and we do not want here to lengthen how to build the model and what its problems and advantages